MEMBUMIKAN QATH’I DAN ZHANNI (Konsep Absolut dan Relativitas Hukum) - Umi Cholifah (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2017)
The problematic society today is very complex when compared with the past. Therefore, it is important to emphasize the Qur'an and the Hadith. Thus, the textual dominance of the two sources is still very strong as any other method of reasoning used. In the study of qath'i and zanni for example, both of them have a purpose to facilitate the classification of the text of Al'Qur'an and Hadith. But this makes the meaning both narrow. Through descriptive normative research methods, the authors describe qath'i and zhanni from some literatures. And then followed by a description of the absolute concept and the relativity of the law, from classical and modern understanding. The result of this research is known that the conceptually the application both of it is different. Qath'i in the the Qur'an concerns the aspect of his arrival of the source / al-wurud truth so that in the Zhanni level only concerns the meaning aspect of the legal content, but in the Hadith, these two aspects are included in the study of Qath'i and Zhanni. In addition, the study of qath'i and zhanni is still very helpful in solving contemporary cases with a record of development in understanding. This is because the concept of qath'i and zhanni is not a method of ijtihad but is a study of ijtihad